Successful HeartMate 3 implantation in isolated right heart failure—first in man experience of right heart configuration - Ricklefs, Marcel; Hanke, Jasmin S.; Dogan, Guenes; Chatterjee, Anamika; Feldmann, Christina; Deniz, Ezin; Korte, Wilhelm; Kirchhoff, Felix; Haverich, Axel; Schmitto, Jan D. (Journal of Thoracic Disease, 2018)
In this article, we present the case of a 72-year-old male patient suffering from a severe form of singular isolated end-stage right heart failure based on arrhythmogenic right ventricular cardiomyopathy (ARVC), who was admitted to our clinic for acute cardiac decompensation.